The occurrence of adverse drug reactions reported for attention deficit hyperactivity disorder (ADHD) medications in the pediatric population: a qualitative review of empirical studies - Aagaard L (Dove Medical Press, 2011)
Lise Aagaard1-3, Ebba Holme Hansen1-31Department of Pharmacology and Pharmacotherapy, Section for Social Pharmacy, Faculty of Pharmaceutical Sciences, University of Copenhagen, Denmark; 2FKL-Research Centre for Quality in Medicine Use, Copenhagen, Denmark; 3Danish Pharmacovigilance Research Project (DANPREP), Copenhagen, DenmarkBackground: To review empirical studies of adverse drug reactions (ADRs) reported to be associated with the use of medications generally licensed for treatment of attention deficit hyperactivity disorder (ADHD) symptoms in the pediatric population.Methods: PubMed, Embase, and PsycINFO® databases were searched from origin until June 2011. Studies reporting ADRs from amphetamine derivates, atomoxetine, methylphenidate, and modafinil in children from birth to age 17 were included. Information about ADR reporting rates, age and gender of the child, type, and seriousness of ADRs, setting, study design, ADR assessors, authors, and funding sources were extracted.Results: The review identified 43 studies reporting ADRs associated with medicines for treatment of ADHD in clinical studies covering approximately 7000 children, the majority of 6- to 12-year-old boys, and particularly in the United States of America (USA). The most frequently reported ADRs were decrease in appetite, gastrointestinal pain, and headache. There were wide variations in reported ADR occurrence between studies of similar design, setting, included population, and type of medication. Reported ADRs were primarily assessed by the children/their parents, and very few ADRs were rated as being serious. A large number of children dropped out of studies due to serious ADRs, and therefore, the actual number of serious ADRs from use of psychostimulants is probably higher. A large number of studies were conducted by the same groups of authors and sponsored by the pharmaceutical companies manufacturing the respective medications.Conclusion: Reported ADRs from use of psychostimulants in children were found in clinical trials of short duration. Since ADHD medications are prescribed for long-term treatment, there is a need for long-term safety studies. The pharmaceutical companies should make all information about ADRs reported for these medications accessible to the public, and further studies are needed on the impact of the link between researchers and the manufacturers of the respective products.Keywords: adverse drug reactions, attention deficit hyperactivity disorder, children, pharmacovigilance